Imiennictwo łemkowskie w XIX wieku - Słabczyński, Robert (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The name resource of Lemkos living in the first half of the nineteenth century is mostly made up of anthroponyms derived from the Christian tradition, i.e. biblical names, as well as names of the holy martyrs and the blessed of different periods of Christianity, belonging more often to Eastern Churches, a little less often to the Catholic Church. Most of the Lemko anthroponyms derive from the Orthodox-Russian tradition, which in turn has its roots in the Greek tradition. Names of Greek etymology account for 50.5% of the excerpted material. The most common ones include the following: Anastasia, Gregor, Basilius, Andreas, Stephanus, Theodorus, Ksenia, Parasceve, Pelagia, Demetrius, Petrus, Helena. Latin names are much less common (19%), e.g. Paulus, Romanus, Antonius, Ignatius, Julia, Julianus, as well as Hebrew names (12,4%), e,g. Maria, Anna, Ewa, Joannes, Symeon. Germanic names (Wilhelmus, Adalbertus, Conradus, Leopoldus) and Slavic names (Stanislaus) were among the rarest. The analyzed anthroponomastics is characterized by high repeatability of names. The proper names in the top ten make up 57.3% of all units. The most frequently repeated names are Maria, Joannes, Anna, Anastasia, Gregorius, Andreas, Theodorus, Stephanus, Simeon. Names which have appeared once represent only 2.3% of the analyzed anthroponomastics.
Keywords: name; anthroponomastics; Lemko